Literary experiments in magazine publishing beyond serialisation - Vranken, Thomas (The nineteenth century series, 2020)
As the nineteenth century came to an end, a number of voices within the British and American magazine industries pushed back against serialisation as the dominant publication mode, experimenting instead with less conventional magazine formats. This book explores these formats, focusing (in particular) on the ways in which the periodical press first published The Adventures of Huckleberry Finn, The Picture of Dorian Gray, and The Return of Sherlock Holmes. What led magazines to publish excerpts from a forthcoming book, or an entire novel in a single issue, or a discontinuous short-story series? How did these experimental modes affect the act of reading? Drawing on a range of archival and other primary sources, Literary Experiments in Magazine Publishing: Beyond Serialization addresses these and other questions